A CASE REPORT ON CHARMADAL THROUGH PANCHAKARMA W.S.R. TO ECZEMA - Parwati; Kavita; Swarnakant jena; Santosh Kumar Bhatted; Prasanth Dharmarajan (International Journal of Ayurveda and Pharma Research, 2020)
Charmadal is a type of Kshudrakushta characterized with symptoms such as redness, itching, pustules, pain and cracks in the skin and tenderness. Most of the symptoms of Eczema can be correlated with Charmadal as mentioned in Ayurvedic classics. A diagnosed case of Eczema came with chief complaints of red patches on skin associated with severe itching, burning and dryness over different body parts (on face, neck, upper arm) since 4 years with complaint of oozing of blood from the patches after itching. No satisfactory treatment is present except topical steroids, but in Ayurveda text line of treatment for Charmadal is present i.e., Virechana Karma”. Before giving Virechana treatment SCORAD (Scoring atopic dermatitis) was 26.55% and after follow up SCORAD 86.05%. Before Virechana treatment DLQI was 25% (extremely large effect on patient’s life) and after follow up DLQI was 4% (small effect on patient life). The results of the study showed that when Virechana Karma was performed, it increased the efficacy of oral Ayurveda medicines in the patient of Charmadal. Virechana improved the condition of patient to very much extent.